Practical tips to manage travel fatigue and jet lag in athletes - Janse van Rensburg, D. C.; Fowler, P.; Racinais, S. (British Journal of Sports Medicine, 2021)
Travel forms an integral part of modern-day athletes lives. The interrelated effects of travel fatigue, jet lag and increased risk of illness, are likely to affect performance unless managed appropriately. Travel fatigue follows any long journey and resolve following a good night`s sleep, but can accumulate with frequent travel. Jet lag ensues misalignment between the internal circadian rhythms and new destination time after rapid travel across more than three time zones, resulting in sleep disruption, daytime fatigue and gastrointestinal disturbances. Sleep loss appears to be central to the detrimental impact of long-haul travel on performance. Additionally, circadian rhythms of numerous psychological and physiological variables with a typical early-morning nadir and late afternoon peak will be misaligned to the new destination time, which, depending on time of competition, could affect performance directly.